2018
DOI: 10.1016/j.aej.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of nanofluid natural convection in a square cavity with a hot obstacle using lattice Boltzmann method

Abstract: In the present work, for the first time, laminar natural convection of water-TiO 2 nanofluid around a hot obstacle in a square cavity is simulated by Lattice Boltzmann Method (LBM). The effect of Rayleigh number, obstacle dimension, volume fraction of nanofluid, cavity dimensions, surface ratio and various models for computing of thermal conductivity coefficient and viscosity coefficient on Nusselt number and heat transfer around hot obstacle in enclosure has been investigated. The results show that by increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Comparison of the obtained average Nusselt number with the results of Rahmati et al[24] at Ra = 10 6 .…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Comparison of the obtained average Nusselt number with the results of Rahmati et al[24] at Ra = 10 6 .…”
mentioning
confidence: 75%
“…The numerical code was then verified by comparing the results with those obtained in two different simulation cases: the first case concerns a three-dimensional cavity with a horizontal gradient of temperature and concentration filled with an aqueous solution Pr = 10, Le = 10 and Ra = 10 5 developed by Sezai and Mohamad [23], and the second one is related to a square cavity of dimension L filled with nanofluids containing a square hot obstacle centered in the cavity with a width W. The Prandtl number is equal to 6.2 and the Rayleigh number is equal to 10 6 . The nanofluid is water-Cu with a fraction of 0.04 [24] (Table 3). It is clear that the results of our code are in good agreement with those proposed by Rahmati and Tahery [24].…”
Section: Grid Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The results displayed Nu increased proportionally with the vent size at low enclosure widths and it is inversely proportional with vent size for high enclosure widths. Rahmati and Tahery [14] investigated the effect of Ra, obstacle dimension, nanofluid volume fraction, cavity dimensions, surface ratio and various models for thermal conductivity coefficient and viscosity coefficient on Nu and heat transfer around hot obstacles in an enclosure for laminar natural convection of water-TiO2 nanofluid using the Lattice Boltzmann Method. The results indicated that the average Nu increased with the increase in Ra and volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Different nano-particle with water was considered. Rahmati and Tahery [8] simulated the laminar natural convection in the cavity flow numerically. They studied water-TiO2 nano-fluid with Lattice-Boltzmann method.…”
Section: Introductionmentioning
confidence: 99%